Fe-doped densely stacked graphene for compact capacitive energy storage - Sinan-Tatli, Neriman; Unur-Yilmaz, Ece (Elsevier Science Sa, 2023)
Herein, we present iron oxide (& alpha;-Fe2O3) etching and simultaneous hydrothermal reduction approach to prepare densely stacked defect-rich graphene with abundant pseudocapacitive heteroatoms (18.1 wt% O and 1.2 wt% Fe). Electrochemical measurements were conducted in acidic (1 M H2SO4) and neutral (1 M Na2SO4) aqueous media. The Fe-doped densely stacked graphene (Fe-rGO) with a low specific surface area (32.9 m2 g-1) and high particle density (1.84 g cm-3) displayed high gravimetric and volumetric capacitances of 425 F g-1 and 780 F cm-3 at 0.25 A g-1, respectively, as well as outstanding rate performance (71 % capacitance retention at 20 A g-1 in 1 M H2SO4). Moreover, Fe-rGO exhibited high electrochemical and structural stability over 5000 cycles at 10 A g-1 without any loss in capacitance. An asymmetric supercapacitor (ASC) with Fe-rGO negative electrode and MnO2/PEDOT:PSS positive electrode was assembled with aqueous 1 M Na2SO4 electrolyte. The device exhibited 17.3 Wh kg-1 specific energy and a long cyclic stability (10,000 cycles at 1 A g-1). A practical application of the device was demonstrated by powering a light emitting diode.
Keywords: Fe-doped graphene; Hydrothermal reaction; Supercapacitors